Experiences, practices and barriers to accessing health information: A qualitative study. (July 2017) - Scantlebury, Arabella; Booth, Alison; Hanley, Bec
Highlights: HPs and patients primarily use the internet to access health information. Health information informs HPs and patients/members of the publics' decision making. A range of barriers to accessing health information were identified. Various 'informal' methods were used to determine information quality. There is a need to ensure that decisions making is based on good quality information. Abstract: Background: With technology advancements making vast amounts of health information available whenever and wherever it is required, there is a growing need to understand how this information is being accessed and used. Objective: Our aim was to explore patients/public and health professionals' experiences, practices and preferences for accessing health information. Methods: Focus groups were conducted with 35 healthcare professionals (31 nurses and 4 allied health professionals) and 14 patients/members of the public. Semi-structured interviews were conducted with 5 consultants, who were unable to attend the focus groups. Data collection took place between March and May 2013 and all data were analysed thematically. Results: Health professionals and patients/members of the public reported primarily accessing health information to inform their decision making for providing and seeking treatment respectively. For all participants the internet was the primary mechanism for accessing health information, with health professionals' access affected by open access charges; time constraints and access to computers. Variation in how patients/members of the public and health professionals appraise the quality of information also emerged, with a range of techniques for assessing quality reported. Conclusions: There was a clear preference for accessing health information online within our sample. Given that this information is central to both patient and health professionals' decision making, it is essential that these individuals are basing their decisions on high quality information. Findings from this study have implications for educationalists, health professionals, policymakers and the public.